Analisis Kinerja Keuangan Pemerintah Daerah Kabupaten Agam Tahun Anggaran 2018-2022 Menurut Perspektif Ekonomi Islam - Yennita, Dylla Sukma; Surmarni, Nini (LPPM - STIE SAKTI ALAM KERINCI, 2024)
This research aims to analyze the Financial Performance of the Regional Government of Agam Regency for the 2018-2022 Fiscal Year when viewed based on: (1) Fiscal Decentralization Degree Ratio, (2) Regional Financial Independence Ratio, (3) PAD Utilization Ratio, (4) Efficiency Ratio Regional Finance, (5) Harmony Ratio. This research is quantitative descriptive research carried out at the Regional Finance and Heritage Agency of Agam Regency. This research uses documentation to collect information. Using quantitative descriptive information analysis methods with the formula for Degree of Fiscal Decentralization Ratio, Regional Financial Independence Ratio, PAD Effectiveness Ratio, Regional Financial Efficiency Ratio, and Harmony Ratio. The research results show that the financial performance of the Agam Regency regional government is not good. This can be seen in the results of the analysis (1) The ratio of the degree of fiscal decentralization is categorized as very low with a percentage of <15%. (2) The ratio of regional financial independence has an instructive relationship pattern because it is categorized as very low with an interval of <15%. This is because the role of the central government still dominates. (3) The PAD efficiency ratio is within the criteria of being quite efficient with criteria of 90% - 99%. (4) The regional financial efficiency ratio is quite effective with an average of 92.30%. (5) The harmony ratio based on surgical expenditure is considered good with an interval of 50% - 100% when compared to capital expenditure with an interval of 0% - 50%, so it can be said that regional governments are still not paying attention to regional development. Keywords: Regional Financial Performance, Degree of Fiscal Decentralization Ratio, Regional Financial Independence Ratio, PAD Effectiveness Ratio, Regional Financial Efficiency Ratio, Harmony Ratio